(untitled) (Al-Academy, 2021)
This research (communicative values of the visual suggestion in TV advertising) presents a precise description for the process of conveying the communicative message through employing the visual suggestion in TV advertisements. This research consists of four chapters. The first chapter includes the research problem which is summarized by the following question: what are the communicative values accomplished in Tv advertisement which produce visual suggestions that raise strangeness and tension in the advertisement? The research importance lies in benefiting the researchers and scholars in the field of TV advertisement direction and the visual suggestion is one the main ways for building the advertisement. It also benefits the relevant institutions and authorities and its role in reinforcing the communicative values. It also contributes to developing the intellectual and methodological visions in keeping pace with development. The research objective is limited to revealing the communicative values of the visual suggestion and its role in TV advertising. The researcher set spatial limits represented by studying a questionnaire for the third year students, evening studies, in the department of advertising techniques/ College of Applied Arts. As for the temporal limit, it is represented by the period 2018-2019. The objective limits (the communicative values of the visual suggestion the TV adverting). The second chapter represents the theoretical framework. It consists of two sections. The first section (communicative values in TV advertising). The second section (visual suggestion in TV advertising). In the third chapter (the research procedures), the analytical descriptive method has been adopted. The research community consists of (100) recipients from the third year students, evening studies, in the department of advertising techniques/ College of Applied Arts. They have been chosen because they are recipients and at the same time they study TV advertisements. The sample has been chosen (50%) from the original community. The researcher used a questionnaire as a tool for the study. Chapter four consists of the results of the study which showed that the majority of the sample see that these advertisements presented to them contain the communicative values of the visual suggestion. They constitute 58% of the total sample.